Analysis of 6,515 exomes reveals the recent origin of most human protein-coding variants - Fu, Wenqing; O’Connor, Timothy D.; Jun, Goo; Kang, Hyun Min; Abecasis, Goncalo; Leal, Suzanne M.; Gabriel, Stacey; Rieder, Mark J.; Altshuler, David; Shendure, Jay; Nickerson, Deborah A.; Bamshad, Michael J.; et al. (Nature (London), 2013)
Resequencing of genes from individuals of European and African American ancestry indicates that approximately 73% of all protein-coding SNVs and approximately 86% of SNVs predicted to be deleterious arose in the past 5,000–10,000 years, and that European Americans carry an excess of deleterious variants in essential and Mendelian disease genes compared to African Americans. Recent genetic change in a human population As part of the NHLBI Exome Sequencing Project, the exomes of more than 6,500 individuals of European American and African American ancestry have been sequenced. Using these data, the authors estimate that about 73% of all protein-coding single nucleotide variants (SNVs) and 86% of SNVs predicted to be deleterious arose in the past 5,000–10,000 years, a short span in evolutionary time that coincides with a period of accelerated population growth. Around 86% of changes predicted to be harmful arose within the same timeframe, with European Americans harbouring more harmful variants in essential and Mendelian disease genes than African Americans. The data suggest that the increased mutational capacity of recent human populations has influenced the burden of Mendelian disorders, but is also likely to promote beneficial genetic changes that will be selected in future generations to come. More practically, the results will be of use in prioritizing potential disease-causing variants in gene-mapping studies. Establishing the age of each mutation segregating in contemporary human populations is important to fully understand our evolutionary history 1 , 2 and will help to facilitate the development of new approaches for disease-gene discovery 3 . Large-scale surveys of human genetic variation have reported signatures of recent explosive population growth 4 , 5 , 6 , notable for an excess of rare genetic variants, suggesting that many mutations arose recently. To more quantitatively assess the distribution of mutation ages, we resequenced 15,336 genes in 6,515 individuals of European American and African American ancestry and inferred the age of 1,146,401 autosomal single nucleotide variants (SNVs). We estimate that approximately 73% of all protein-coding SNVs and approximately 86% of SNVs predicted to be deleterious arose in the past 5,000–10,000 years. The average age of deleterious SNVs varied significantly across molecular pathways, and disease genes contained a significantly higher proportion of recently arisen deleterious SNVs than other genes. Furthermore, European Americans had an excess of deleterious variants in essential and Mendelian disease genes compared to African Americans, consistent with weaker purifying selection due to the Out-of-Africa dispersal. Our results better delimit the historical details of human protein-coding variation, show the profound effect of recent human history on the burden of deleterious SNVs segregating in contemporary populations, and provide important practical information that can be used to prioritize variants in disease-gene discovery.